Current collector and preparation method thereof
By forming a multi-layered current collector on aluminum foil and plating copper layers using magnetron sputtering and electroplating technology, the problem of unstable connection between positive and negative current collectors is solved, the mechanical strength and overcurrent capacity of the current collectors are improved, the battery life is extended and the battery performance is improved.
Patent Information
- Application Number
- CN202411794818.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-07
AI Technical Summary
In the prior art, there is a lack of a stable connection between positive and negative current collectors, which leads to the disengagement of the active material layer or the electrolyte during the use of the battery, which easily leads to local side reactions and electrochemical corrosion, affecting the battery life and performance.
By forming a multi-layered current collector on the aluminum foil, including a first alumina layer, an aluminum layer, a second alumina layer and a copper layer, the copper layer is plating using magnetron sputtering and electroplating technology, the bond strength of the aluminum layer and the copper layer is enhanced, and the mechanical strength and overcurrent capability of the current collector are improved.
The mechanical strength and overcurrent capability of the current collector are improved, local side reactions and electrochemical corrosion occur, extended battery life, and improved series conduction capacity between battery cells.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, in particular to a current collector and a preparation method thereof. Background Art
[0002] With the continuous development of solid-state battery technology, achieving high voltage output has become an important research direction. In solid-state batteries, the series connection of multiple battery cells is an effective means to achieve high voltage output.
[0003] In the prior art, the traditional series connection method, that is, stacking the positive and negative current collectors and simply contacting them, has certain defects. Under this design, there is a lack of a stable connection between the positive and negative current collectors. Once the active material layer or electrolyte is separated during the use of the battery, these separated substances can easily enter the gap between the positive and negative current collectors, thereby causing local side reactions and electrochemical corrosion, seriously affecting the life and performance of the battery.
[0004] To overcome this defect, researchers have tried a variety of alternative solutions. One approach is to directly roll the copper and aluminum layers together to achieve a tighter bond. However, due to the difference in the elongation of the two metal materials, this method results in unsatisfactory bonding strength between the two after compounding. Another option is to evaporate aluminum on copper foil, but this approach often results in a higher overall mass density of the current collector because the copper layer is much thicker than the aluminum layer, which not only reduces the energy density of the battery but also increases manufacturing costs.
[0005] In summary, it is of great significance to improve the mechanical strength, flow capacity and structural stability of the current collector and avoid the above-mentioned problems to obtain a current collector. Summary of the invention
[0006] The object of the present invention is to provide a current collector and a preparation method thereof to solve the problems raised in the above background technology.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: A current collector, the structure of which from top to bottom includes a first aluminum oxide layer, an aluminum layer, a second aluminum oxide layer and a copper layer; the copper layer includes a first copper layer and a second copper layer; the thickness of the first aluminum oxide layer is greater than that of the second aluminum oxide layer, and the thickness of the aluminum layer is greater than that of the copper layer.
[0008] More optimally, the aluminum layer has a thickness >20 μm; the second aluminum oxide layer has a thickness <1 μm; and the copper layer has a thickness <10 μm.
[0009] More optimally, the second aluminum oxide layer does not completely cover the surface of the aluminum layer, the second aluminum oxide layer has multiple through holes or blind holes in the planar direction, part or all of the copper layer is at least partially embedded in the through holes or blind holes, and part or all of the copper layer is in direct contact with the aluminum layer.
[0010] Preferably, the preparation of a current collector as claimed in any one of claims 1 to 3 comprises the following steps: S1: Take an aluminum foil with natural aluminum oxide layers on both sides and set it aside; the area of the aluminum foil that is not the natural aluminum oxide layer is the aluminum layer; S2: The natural aluminum oxide layer on one side of the aluminum foil is used as the first aluminum oxide layer; in a vacuum environment or under the protection of an inert gas, the natural aluminum oxide layer on the other side of the aluminum foil is thinned to obtain a second aluminum oxide layer; this is used as the pretreated aluminum foil; S3: In a vacuum environment or under the protection of an inert gas, magnetron sputtering copper is plated on the surface of the second aluminum oxide layer of the pretreated aluminum foil to obtain a first copper layer; electroplating copper on the surface of the first copper layer with an electrolyte to obtain a second copper layer; and obtaining a current collector.
[0011] Among them, the thinning process of the natural aluminum oxide layer is preferably carried out in a vacuum environment or under the protection of an inert gas, and S3 is entered in a vacuum environment or under the protection of an inert gas to avoid the exposed aluminum layer reacting with the air after the natural aluminum oxide layer is thinned to generate aluminum oxide again.
[0012] More optimally, in S2, the thinning treatment method includes one of corona, ion sputtering, and pickling.
[0013] More optimally, when the thinning treatment method is pickling, the specific process is: in a vacuum environment or under the protection of an inert gas, the aluminum foil is placed on a roller, and a pickling solution is dynamically sprayed on the natural aluminum oxide layer on the other side of the aluminum foil to perform shower etching; then dynamically water washing, drying, and winding are performed to obtain a second aluminum oxide layer; this is used as the pre-treated aluminum foil.
[0014] More optimally, the pickling solution includes the following components: by weight percentage, 6-10wt% hydrochloric acid, 0.4-0.6wt% sulfuric acid, and the rest is water; the temperature of the pickling solution shower etching is 75-85°C; when the pickling solution is sprayed, the running speed of the aluminum foil on the roller is 0.04-0.06m / s.
[0015] In a further scheme, the natural aluminum oxide layer on the surface of the aluminum layer is thinned only on one side, because the side that does not need copper plating is the positive electrode side. If this side is also thinned, it is difficult to avoid plating some copper metal during the electroplating process. In the battery system, if there is copper on the positive electrode side, under the condition of high positive potential (>3v), the copper metal is easy to undergo oxidation reaction with the battery system and precipitate into the electrolyte as a heavy metal, contaminating the electrolyte.
[0016] Among them, pickling is selected for thinning the natural aluminum oxide layer. The pickling process can improve the surface roughness of the aluminum foil. During the subsequent copper plating, after the copper ions are deposited, the rough surface pits are embedded by the copper ions, thereby improving the bonding strength between the copper layer and the aluminum layer. Water washing is added after pickling. The water washing process can prevent the pickling liquid from over-pickling the natural aluminum oxide layer, and can also prevent the pickling liquid remaining on the pickling side from contaminating the first aluminum oxide layer on the unpickled side during winding, thereby causing the first aluminum oxide layer on the unpickled side to be destroyed.
[0017] In a further scheme, when the thinning treatment method is ion sputtering, the specific process is: setting the ion source power to 1.5~2.5kw and the bombardment speed to 1.5~2.5m / s, and performing plasma bombardment treatment on the surface of the first aluminum oxide layer under the aluminum foil by running the winding ion source system of the winding vacuum magnetron sputtering coating equipment.
[0018] More optimally, the process parameters of magnetron sputtering copper plating of the first copper layer are: vacuum plating is 2.5×10 -1 ~3.5×10 -1 Pa, negative bias voltage is 125~135V, the distance between copper target and aluminum foil is 15~25cm, plating speed is 2.5~3.5m / min, and target current is 10~20A.
[0019] More optimally, the electrolyte in the copper electroplating process of the second copper layer is a copper sulfate electrolyte, and the copper sulfate electrolyte includes the following components: 195-205 g / L copper sulfate, 75-85 g / L sulfuric acid, 35-45 ppm chloride ions, and 0.02-0.04 g / L collagen.
[0020] Compared with the prior art, the present invention has the following beneficial effects: 1. This solution combines the positive and negative current collectors, and combines the aluminum layer and the copper layer into one current collector. This can improve the problem of local side reactions and local electrochemical corrosion caused by the separation of the active material layer or the separation of the electrolyte into the gap between the positive and negative current collectors during the use of the solid-state battery, thereby extending the battery life. At the same time, after the positive and negative current collectors are combined into one layer, the current capacity of the battery cells in series conduction is also improved.
[0021] 2. This solution can avoid the problem in the prior art that when the copper layer and the aluminum layer are directly rolled into a composite, the bonding strength between them is very poor due to the different elongations of the two metal materials, by plating copper on the surface of the aluminum layer. It can also avoid the problem in the prior art that aluminum is evaporated on copper foil, and the thickness of the copper layer is much greater than that of aluminum, which will make the mass density of the current collector larger, reduce the energy density of the battery, and increase the cost.
[0022] 3. This solution uses copper plating on one side of the aluminum layer. The aluminum layer is relatively thick to ensure the structural strength of the current collector. Before copper plating, the natural aluminum oxide layer on one side of the aluminum layer is thinned. The thinning process requires the removal of part of the aluminum oxide layer. The reason is that after copper particles are sputtered onto the surface of the aluminum layer, they can form a metal bond with aluminum with a high bonding force at a higher sputtering energy. If they are directly sputtered onto the aluminum oxide layer, copper and aluminum oxide are only bonded through intermolecular forces, and the bonding strength is poor. In addition, the conductivity of the natural aluminum oxide layer is poor. Removing the natural aluminum oxide layer can improve the current flow capacity of the current collector. However, the natural aluminum oxide layer cannot be removed excessively. Commonly used thinning methods such as corona, acid pickling or ion sputtering cannot accurately control the uniformity of the removal thickness. If it is removed excessively, the aluminum layer itself will be thinned, resulting in more defects on the surface of the aluminum layer. The aluminum layer is the main part to ensure the strength of the current collector structure. If the aluminum layer has many defects, in the process of preparing the electrode sheet from the current collector, it is easy to break the belt during the rolling and winding processes. During the use of the battery, local bending may also occur, resulting in failure of the electrolyte sealing structure, electrolyte leakage and short circuit and other problems.
[0023] 4. In this scheme, copper plating is preferably divided into two steps. Although part of the aluminum layer is exposed on one side of the second aluminum oxide layer, it has met the conductivity requirements and can be directly electroplated. However, since the exposed aluminum layer is limited in area and unevenly distributed, in order to improve the quality of copper plating, preliminary copper plating is first performed by magnetron sputtering, which can not only improve the conductivity of the current collector, which is beneficial to the uniformity of the next electroplating, but also improve the bonding strength between the copper layer and the aluminum layer, and also improve the coating efficiency (the coating efficiency and cost advantages of electroplating are higher than those of magnetron sputtering). DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] It should be noted that the following parts are parts by mass, and all raw material purchase manufacturers involved in the present invention are not subject to any special restrictions. Examples include: In the following examples, the specification of the aluminum foil is 40 μm.
[0026] In the following embodiments, it is particularly noted that the relevant material parameters are as follows: the copper sulfate electrolyte includes: copper sulfate with a concentration of 200 g / L, sulfuric acid with a concentration of 80 g / L, chloride ions with a volume concentration of 40 ppm, and collagen with a concentration of 0.03 g / L.
[0027] Embodiment 1: A current collector comprising the following steps: Step 1: Select a 40 μm thick aluminum foil, on both sides of which there are 2 μm thick natural aluminum oxide layers obtained by natural oxidation; Step 2: The natural aluminum oxide layer on one side of the aluminum foil is used as the first aluminum oxide layer; under nitrogen protection, 8wt% hydrochloric acid and 0.5wt% sulfuric acid at 80°C are selected as the pickling solution, the aluminum foil is placed on a roller, and the pickling solution is dynamically sprayed on the natural aluminum oxide layer on the other side of the aluminum foil at a running speed of 0.05m / s on the roller, and a row of nozzles are set with the nozzle design perpendicular to the running direction of the aluminum foil to completely cover the width of the aluminum foil for shower etching; Step 3: A water washing station is designed behind the pickling station to clean the pickling liquid remaining on one side of the surface after pickling by spraying. The spraying method is dynamic spraying. The aluminum foil is conveyed under the nozzle filled with water for showering. The nozzle is designed to set a row of nozzles perpendicular to the conveying direction of the aluminum foil, which can completely cover the width of the aluminum foil; the distance between the water washing nozzle and the pickling nozzle is 2m; after water washing, it is dried at 100°C and then rolled up; after pickling, a second aluminum oxide layer with a thickness of less than 200nm is obtained; this is used as the pre-treated aluminum foil; Step 4: Under the protection of high-purity argon, copper is plated on the surface of the second alumina layer by magnetron sputtering. The flow controller is adjusted to stabilize the vacuum degree of the vacuum chamber at 3×10 -1 Pa, a negative bias voltage is applied to the aluminum foil, the negative bias voltage is adjusted to 130 V, the distance between the copper target and the aluminum foil is set to 20 cm, the plating speed is 3 m / min, and the target current is 15 A; a first copper layer with a copper plating thickness of 90 nm is obtained; Step 5: The copper layer is thickened by electrolysis of copper sulfate. The first copper layer obtained above is completely immersed in a copper sulfate electrolyte at a temperature of 40° C. for water electroplating to obtain a second copper layer with a copper plating thickness of 1.1 μm; and a current collector is obtained.
[0028] Embodiment 2: A current collector comprising the following steps: Step 1: Select a 40 μm thick aluminum foil, on both sides of which there are 2 μm thick natural aluminum oxide layers obtained by natural oxidation; Step 2: The natural aluminum oxide layer on one side of the aluminum foil is used as the first aluminum oxide layer; under nitrogen protection, the ion source power is adjusted to 2 kW, and the roll ion source system of the roll-to-roll vacuum magnetron sputtering coating equipment is operated at a bombardment speed of 2 m / s to perform plasma bombardment treatment on the single-side surface of the aluminum foil; Step 3: Design a water washing station. The spraying method is dynamic spraying. The aluminum foil is conveyed under a nozzle filled with water for showering. The nozzle is designed to set a row of nozzles perpendicular to the conveying direction of the aluminum foil, which can completely cover the width of the aluminum foil. The distance between the water washing nozzle and the acid washing nozzle is 2m. After water washing, it is dried at 100℃ and then rolled up. A second aluminum oxide layer with a thickness of less than 200nm is obtained. This is used as the pre-treated aluminum foil. Step 4: Under the protection of high-purity argon, copper is plated on the surface of the second alumina layer by magnetron sputtering. The flow controller is adjusted to stabilize the vacuum degree of the vacuum chamber at 3×10 -1 Pa, a negative bias voltage is applied to the aluminum foil, the negative bias voltage is adjusted to 130 V, the distance between the copper target and the aluminum foil is set to 20 cm, the plating speed is 3 m / min, and the target current is 15 A; a first copper layer with a copper plating thickness of 90 nm is obtained; Step 5: The copper layer is thickened by electrolysis of copper sulfate. The first copper layer obtained above is completely immersed in a copper sulfate electrolyte at a temperature of 40° C. for water electroplating to obtain a second copper layer with a copper plating thickness of 1.1 μm; and a current collector is obtained.
[0029] Embodiment 3: A current collector comprising the following steps: Step 1: Select a 40 μm thick aluminum foil, on both sides of which there are 2 μm thick natural aluminum oxide layers obtained by natural oxidation; Step 2: The natural aluminum oxide layer on one side of the aluminum foil is used as the first aluminum oxide layer; under nitrogen protection, 80°C 8wt% hydrochloric acid and 0.5wt% sulfuric acid are selected as the pickling solution, the aluminum foil is placed on a roller, and the pickling solution is dynamically sprayed on the natural aluminum oxide layer on the other side of the aluminum foil at a running speed of 0.05m / s on the roller, and a row of nozzles are set perpendicular to the running direction of the aluminum foil to completely cover the width of the aluminum foil for shower etching; after pickling, a second aluminum oxide layer with a thickness of less than 200nm is obtained; this is used as the pre-treated aluminum foil; Step 3: Under the protection of high-purity argon, the surface of the second alumina layer is copper plated by magnetron sputtering. The flow controller is adjusted to stabilize the vacuum degree of the vacuum chamber at 3×10 -1 Pa, a negative bias voltage is applied to the aluminum foil, the negative bias voltage is adjusted to 130 V, the distance between the copper target and the aluminum foil is set to 20 cm, the plating speed is 3 m / min, and the target current is 15 A; a first copper layer with a copper plating thickness of 90 nm is obtained; Step 4: copper sulfate electrolysis is used to thicken the copper layer. The first copper layer obtained above is completely immersed in a copper sulfate electrolyte at a temperature of 40° C. for water electroplating to obtain a second copper layer with a copper plating thickness of 1.1 μm; and a current collector is obtained.
[0030] Comparative Example 1: Based on Example 1, both sides of the aluminum foil were pickled at the same time, and the aluminum oxide layer on both sides after pickling was less than 200 nm, and the other processes remained unchanged, specifically: Step 1: Select a 40 μm thick aluminum foil, on both sides of which there are 2 μm thick natural aluminum oxide layers obtained by natural oxidation; Step 2: The natural aluminum oxide layer on both sides of the aluminum foil is used as the first aluminum oxide layer; under nitrogen protection, 8wt% hydrochloric acid and 0.5wt% sulfuric acid at 80°C are selected as the pickling solution, the aluminum foil is placed on the roller, and the pickling solution is dynamically sprayed on the natural aluminum oxide layer on both sides of the aluminum foil at a running speed of 0.05m / s on the roller, and a row of nozzles are set with the nozzle design perpendicular to the running direction of the aluminum foil to completely cover the width of the aluminum foil for shower etching; Step 3: A water washing station is designed behind the pickling station to clean the pickling liquid remaining on the two surfaces after pickling by spraying. The spraying method is dynamic spraying. The aluminum foil is conveyed under the nozzle filled with water for showering. The nozzle is designed to set a row of nozzles perpendicular to the conveying direction of the aluminum foil, which can completely cover the width of the aluminum foil; the distance between the water washing nozzle and the pickling nozzle is 2m; after water washing, it is dried at 100°C and then rolled up; after pickling, a second aluminum oxide layer with a thickness of less than 200nm is obtained; this is used as the pre-treated aluminum foil; Step 4: Under the protection of high-purity argon, copper is plated on the surface of the second alumina layer by magnetron sputtering. The flow controller is adjusted to stabilize the vacuum degree of the vacuum chamber at 3×10 -1 Pa, a negative bias voltage is applied to the aluminum foil, the negative bias voltage is adjusted to 130 V, the distance between the copper target and the aluminum foil is set to 20 cm, the plating speed is 3 m / min, and the target current is 15 A; a first copper layer with a copper plating thickness of 90 nm is obtained; Step 5: The copper layer is thickened by electrolysis of copper sulfate. The first copper layer obtained above is completely immersed in a copper sulfate electrolyte at a temperature of 40° C. for water electroplating to obtain a second copper layer with a copper plating thickness of 1.1 μm; and a current collector is obtained.
[0031] Comparative Example 2: Based on Example 1, the thickness of the aluminum layer is less than the thickness of the copper layer, and the other processes remain unchanged, specifically: Step 1: Select a 2 μm thick aluminum foil, on both sides of which there are natural aluminum oxide layers of 1 μm thick obtained by natural oxidation; Step 2: The natural aluminum oxide layer on one side of the aluminum foil is used as the first aluminum oxide layer; under nitrogen protection, 8wt% hydrochloric acid and 0.5wt% sulfuric acid at 80°C are selected as the pickling solution, the aluminum foil is placed on a roller, and the pickling solution is dynamically sprayed on the natural aluminum oxide layer on the other side of the aluminum foil at a running speed of 0.05m / s on the roller, and a row of nozzles are set with the nozzle design perpendicular to the running direction of the aluminum foil to completely cover the width of the aluminum foil for shower etching; Step 3: A water washing station is designed behind the pickling station to clean the pickling liquid remaining on one side of the surface after pickling by spraying. The spraying method is dynamic spraying. The aluminum foil is conveyed under the nozzle filled with water for showering. The nozzle is designed to set a row of nozzles perpendicular to the conveying direction of the aluminum foil, which can completely cover the width of the aluminum foil; the distance between the water washing nozzle and the pickling nozzle is 2m; after water washing, it is dried at 100°C and then rolled up; after pickling, a second aluminum oxide layer with a thickness of less than 100nm is obtained; this is used as the pre-treated aluminum foil; Step 4: Under the protection of high-purity argon, copper is plated on the surface of the second alumina layer by magnetron sputtering. The flow controller is adjusted to stabilize the vacuum degree of the vacuum chamber at 3×10 -1 Pa, a negative bias voltage is applied to the aluminum foil, the negative bias voltage is adjusted to 130 V, the distance between the copper target and the aluminum foil is set to 20 cm, the plating speed is 3 m / min, and the target current is 15 A; a first copper layer with a copper plating thickness of 90 nm is obtained; Step 5: The copper layer is thickened by copper sulfate electrolysis. The first copper layer obtained above is completely immersed in a copper sulfate electrolyte at a temperature of 40° C. for water electroplating to obtain a second copper layer with a copper plating thickness of 3 μm; and a current collector is obtained.
[0032] Comparative Example 3: Based on Example 1, only one copper layer is plated, and the copper layer is not electroplated to be thickened, and the other processes remain unchanged, specifically: Step 1: Select a 40 μm thick aluminum foil, on both sides of which there are 2 μm thick natural aluminum oxide layers obtained by natural oxidation; Step 2: The natural aluminum oxide layer on one side of the aluminum foil is used as the first aluminum oxide layer; under nitrogen protection, 8wt% hydrochloric acid and 0.5wt% sulfuric acid at 80°C are selected as the pickling solution, the aluminum foil is placed on a roller, and the pickling solution is dynamically sprayed on the natural aluminum oxide layer on the other side of the aluminum foil at a running speed of 0.05m / s on the roller, and a row of nozzles are set with the nozzle design perpendicular to the running direction of the aluminum foil to completely cover the width of the aluminum foil for shower etching; Step 3: A water washing station is designed behind the pickling station to clean the pickling liquid remaining on one side of the surface after pickling by spraying. The spraying method is dynamic spraying. The aluminum foil is conveyed under the nozzle filled with water for showering. The nozzle is designed to set a row of nozzles perpendicular to the conveying direction of the aluminum foil, which can completely cover the width of the aluminum foil; the distance between the water washing nozzle and the pickling nozzle is 2m; after water washing, it is dried at 100°C and then rolled up; after pickling, a second aluminum oxide layer with a thickness of less than 200nm is obtained; this is used as the pre-treated aluminum foil; Step 4: Under the protection of high-purity argon, copper is plated on the surface of the second alumina layer by magnetron sputtering. The flow controller is adjusted to stabilize the vacuum degree of the vacuum chamber at 3×10 -1Pa, apply a negative bias to the aluminum foil, adjust the negative bias voltage to 130 V, set the distance between the copper target and the aluminum foil to 20 cm, the plating speed to 3 m / min, and the target current to 15 A; obtain a first copper layer with a copper plating thickness of 90 nm; and obtain a current collector.
[0033] Testing experiment: The current collector prepared in Examples 1 to 3 and Comparative Example 1 was subjected to peeling force test, tensile strength test and mapping test; specifically: (1) Peeling force test: A test sample with a size of 15×100 mm was taken from the current collector prepared in Examples 1 to 3 and Comparative Example 1, and 3M-9080A-15mm tape was attached to a stainless steel plate, and then the aluminum side of the test sample was evenly attached to the double-sided tape, and a 2kg standard small pressure roller was used to squeeze back and forth twice, and then 3M-9080A-14mm tape was attached to the test sample. Paste it on the copper side surface of the sample, use a 2kg standard small pressure roller to squeeze it back and forth twice, then take the pressed sample to a tensile machine and stretch it 180°, the speed is 100mm / min, the width is set to 14mm, and the result is the maximum value, as shown in Table 1; (2) Tensile strength test: The current collector prepared in Examples 1 to 3 and Comparative Example 1 is tested using an electronic universal material testing machine. The test conditions are a gauge length of 10mm, a tensile speed of 100mm / nin, and a width of 15mm. Other requirements are measured according to the method specified in GB / T1040.3-2006, as shown in Table 1; (3) Scanning electronic photography is performed on the aluminum layer surface of the sample, and a mapping test is performed at a magnification of 5000 times. The following parameters are set: the acceleration voltage is 25kV, the beam density is 1nA, the acquisition time is 60s, the element is specified as Cu, and three test points are taken for one sample to obtain the element content of Cu in these three areas, as shown in Table 1.
[0034] The test results are shown in the table:
[0035] Result analysis: According to the data analysis in Table 1, it can be seen that compared with Example 1, Example 2 selects plasma sputtering to remove the aluminum oxide layer on one side, which will reduce the surface roughness of the aluminum foil, so the bonding strength with copper is not as good as that of Example 1, which is reflected in the decrease in peeling force; Compared with Example 1, Example 3 is not washed with water after pickling, and the aluminum oxide layer on the pickled side is thinner, but the aluminum layer in some areas is excessively corroded, and the other side is not pickled but is still corroded by the residual acid on the adjacent side after winding, resulting in a trace amount of copper being plated on the aluminum side during subsequent copper plating. It is reflected in a slight increase in peeling force, a decrease in tensile strength, and copper element is measured in the Mapping test. Compared with Example 1, both sides of Comparative Example 1 are pickled, and the roughness of both sides increases after pickling, the thickness of the aluminum foil is unevenly distributed, and the surface of the aluminum side is plated with copper elements during subsequent copper plating. It is reflected in a decrease in tensile strength, and the copper element is measured in the Mapping test and is greater than that of Example 3. Comparative Example 2 Since the initial aluminum foil is too thin and there are many surface defects of the aluminum foil after pickling, the high temperature generated by the magnetron in the subsequent magnetron sputtering copper plating process causes micropores on the surface of the aluminum foil. The copper layer cannot be electroplated to thicken the micropores, resulting in poor tensile strength and peeling strength of the finished current collector. Comparative Example 3 Since there is only one layer of magnetron sputtering copper layer, the tensile strength of the product current collector is poor and the peeling strength is also poor.
[0036] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A current collector, characterized in that: The structure of the current collector includes a first aluminum oxide layer, an aluminum layer, a second aluminum oxide layer and a copper layer from top to bottom; the copper layer includes a first copper layer and a second copper layer; the thickness of the first aluminum oxide layer is greater than that of the second aluminum oxide layer, and the thickness of the aluminum layer is greater than that of the copper layer.
2. A current collector according to any one of claim 1, characterized in that: The thickness of the aluminum layer is greater than 20 μm; the thickness of the second aluminum oxide layer is less than 1 μm; and the thickness of the copper layer is less than 10 μm.
3. A current collector according to claim 1, characterized in that: The second aluminum oxide layer does not completely cover the surface of the aluminum layer. The second aluminum oxide layer has multiple through holes or blind holes in the planar direction. Part or all of the copper layer is at least partially embedded in the through holes or blind holes. Part or all of the copper layer is in direct contact with the aluminum layer.
4. A method for preparing a current collector, characterized in that: Preparation of a current collector according to any one of claims 1 to 3 The following steps are involved: S1: Take an aluminum foil with natural aluminum oxide layers on both sides and set it aside; the area of the aluminum foil that is not the natural aluminum oxide layer is the aluminum layer; S2: The natural aluminum oxide layer on one side of the aluminum foil is used as the first aluminum oxide layer; in a vacuum environment or under the protection of an inert gas, the natural aluminum oxide layer on the other side of the aluminum foil is thinned to obtain a second aluminum oxide layer; this is used as the pretreated aluminum foil; S3: In a vacuum environment or under the protection of an inert gas, magnetron sputtering copper is plated on the surface of the second aluminum oxide layer of the pretreated aluminum foil to obtain a first copper layer; electroplating copper on the surface of the first copper layer with an electrolyte to obtain a second copper layer; and obtaining a current collector.
5. A method for preparing a current collector according to claim 4, characterized in that: In S2, the thinning treatment method includes one of corona, ion sputtering, and pickling.
6. A method for preparing a current collector according to claim 5, characterized in that: When the thinning treatment is pickling, the specific process is: placing the aluminum foil on a roller in a vacuum environment or under the protection of an inert gas, dynamically spraying a pickling liquid on the natural aluminum oxide layer on the other side of the aluminum foil, and performing shower etching; Then it is dynamically washed with water, dried and rolled up to obtain a second aluminum oxide layer; this is the pretreated aluminum foil.
7. A method for preparing a current collector according to claim 6, characterized in that: The pickling solution comprises the following components: by weight percentage, 6-10wt% hydrochloric acid, 0.4-0.6wt% sulfuric acid, and the rest water; the temperature of the pickling solution shower etching is 75-85°C; when the pickling solution is sprayed, the running speed of the aluminum foil on the roller is 0.04-0.06m / s.
8. The method for preparing a current collector according to claim 4, characterized in that: The process parameters of magnetron sputtering copper plating of the first copper layer are: vacuum plating is 2.5×10 -1 ~3.5×10 -1 Pa, negative bias voltage is 125~135V, the distance between copper target and aluminum foil is 15~25cm, plating speed is 2.5~3.5m / min, and target current is 10~20A.
9. A method for preparing a current collector according to claim 4, characterized in that: The electrolyte in the copper electroplating process of the second copper layer is a copper sulfate electrolyte, and the copper sulfate electrolyte includes the following components: 195-205 g / L copper sulfate, 75-85 g / L sulfuric acid, 35-45 ppm chloride ions, and 0.02-0.04 g / L collagen.